Da proteção permanente das áreas ciliares aos recursos hídricos em meio ambiente urbano consolidado estudo de caso Arroio Pinhal – Caxias do Sul/ RS - Pedone, Carlos Eduardo Mesquita (My University, 2023)
Water resources in urban environments have been employed without distinction for the disposal of sanitary, industrial, and stormwater sewage. Its margins end up - for reasons diverse - not being designated as Permanent Preservation Areas [APP] as the legislation in place would require. We understand that existing juridical instruments of Urban Policy such as municipal planning, instruments of Environmental Policy, and juridico-political instruments in the scope of Fiscal and Tax Policies, when used in a combined fashion, in the context of a Consorted Urban Operation [OUC], may promote the protection of areas adjacent to water resources within consolidated urban environments. The approach being proposed here is an alternative to the currently prevalent notion, one of negation of the ecological function of certain sectors of the city due to them being understood as consolidated urban areas. In opposition to this acritical outlook stands a regard towards intangible values, such as ecological welfare, quality of life improvement, and increased biodiversity within the wider concept of environmentally sustainable cities. The goal is to achieve structural urban transformation, social improvement, and environmental promotion in these areas thus enabling the reclaiming of an ecological function to sections of the city. The present work intends to develop a technical and juridical set of tools to support policymaking in regard to the issues abovementioned. The methodology employed herein stems from the case study of the Permanent Preservation Areas in the Arroio Pinhal microbasin in Caxias do Sul, RS. The study first maps the microbasin as a whole and then proceeds on successive scales of approximation, thus allowing the identification of the component elements and the systematization of typical situations; the systematization is done by sector based on the current uses of public and private lands. The specific characteristics of each sector, the uses of the soil, and the type activity performed therein are identified and a system of categorization is proposed, thus contributing to the regulation of the Arroio Pinhal Zone of Environmental Interest [ZIAM] as prescribed by the Integrated Development Master Plan [PDDI] of the municipality of Caxias do Sul. The present proposal seeks to build a specific legal regime that is able of being replicated in problems of a similar nature, which are characteristic of the occupation of the land in our region, in respect to the water resources in consolidated urban environments. [resumo fornecido pelo autor]
Os recursos hídricos no meio ambiente urbano têm sido utilizados, indistintamente, para disposição de esgoto cloacal e industrial bem como drenagem urbana. Suas margens, por motivos diversos, acabam não sendo protegidas como Áreas de Preservação Permanente, de acordo com o que preconiza a norma vigente. Entende-se que instrumentos jurídicos de planejamento municipal da Política Urbana, instrumentos da Política Ambiental e institutos jurídico políticos na esfera da Política Fiscal Tributária existentes, utilizados de forma combinada, no âmbito de uma Operação Urbana Consorciada, podem promover a proteção das áreas ciliares aos recursos hídricos em meio ambiente urbano consolidado. A abordagem proposta busca uma alternativa à ideia hoje prevalente de negação da função ecológica de setores da cidade, por conta do seu reconhecimento como área urbana consolidada. Essa visão acrítica tem como contraponto o olhar sobre valores intangíveis - como benefício ecológico, melhoria da qualidade de vida e aumento da biodiversidade - dentro de um conceito mais amplo de cidade ambientalmente sustentável. O objetivo consiste em alcançar, nessas áreas, transformações urbanísticas estruturais, melhorias sociais e valorização ambiental, propiciando a recuperação da função ecológica de setores da cidade. O presente trabalho tem como objetivo criar um instrumental jurídico e técnico de suporte à decisão para abordagem desse problema como Política Pública. A metodologia proposta parte do estudo de caso por meio do mapeamento da microbacia como um todo e, após, avança em escalas sucessivas de aproximação, permitindo que se identifiquem as partes e se sistematizem situações típicas por setor a partir das funções atuais da terra pública e privada. As características específicas de cada setor, os usos do solo e as atividades são identificadas e sistematizadas no estudo de caso das Áreas de Preservação Permanente da Microbacia do Arroio Pinhal, seus afluentes e tributários, em Caxias do Sul/RS, contribuindo para o regramento específico da Zona de Interesse Ambiental - ZIAM, previsto no Plano Diretor de Desenvolvimento Integrado - PDDI. A proposta objetiva construir um regime jurídico específico para as situações típicas que possa ser replicado em problemas de mesma natureza em outros casos que são característicos da ocupação do solo na nossa região, junto aos recursos hídricos em meio urbano consolidado. [resumo fornecido pelo autor]
Keywords: Direito urbanístico; Política pública (Direito); Meio ambiente - Aspectos jurídicos; Área de preservação permanente (APP); Urbanização - Aspectos ambientais; City planning and redevelopment law; Public policy (Law); Environment - Legal aspects; Permanent preservation area (APP); Urbanization - Environmental aspects